STUDENT’S FOLK MUSIC BAND: TECHNOLOGY OF GROUP INTERPRETATION OF MUSICAL COMPOSITION - Malakhova, Margaryta (Educological discourse, 2019)
The article deals with the problem of collaboration and group interaction during the production of a musical composition. The terms “music band”, “pedagogic technology” and “interpretation” are revealed. Based on author’s experience, the technological dimensions in the activity of student’s folk music band are shown. These dimensions are aimed at performance of musical compositions during collective interactions. According to this problem the four main stages are market out, such as familiarization with a musical composition, technical mastering, realization of artistic content and music performance. It is stressed, that performance interpretation covers all possibilities of musician. Thus for the sake of realization owns ideas it is necessary to have professional skills. Among them we point out creative thinking, performance skills, including ensemble mastering, possibilities, specifically good ear for music, and psychological stability, i.e. the high level of self-regulation during public performances. The main part of the article shows theoretical grounds, methodological recommendation and practical advice as for formation of collective thinking and common masterly performance. It is stressed, that necessary condition of good activity of student group is implementation of methods and tasks directed at development of creative individuality of every folk music band member, improvement of masterly performance and increasing of psychological stability during the performances. It is pointed out that team work during permanent cooperation creates band performance style and makes the conditions for generalization of masterly performance and development of creative potential, intuition and artistic feeling.